China's India Policy: The Importance of Bilateralism— An Appraisal. (June 2019) - Surie, Nalin
Given the essential positive history of China's relations with India, China's world view and the fact of geographical contiguity, the essential approach that China follows vis-à-vis India post 1949 is based on bilateralism. The bilateral approach has defined China's negotiations over the border as well as economic relations between the two. In the past bilateralism has allowed China to consolidate its control over Tibet and follow a mercantilist economic policy vis- a- vis India. But the change in the geopolitical status of both nations indicates that bilateral relations, after Wuhan, have been reset to represent those between two 'major powers' who have broader regional and global interests as well. Although bilateralism will continue to underline their policies towards each other in matters of common development, regional development or the building of a community with a shared future for humanity, China will need to redefine its approach to bilateralism by broadening and deepening it to create a truly mutual relationship.